Separation of Four Flavonoid Glycosides from Hydrocotyle sibthorpioides Lam. by High-speed Counter-current Chromatography - Daoguang SONG; Zhi CHEN (Shipin gongye ke-ji, 2022)
For an improved study of flavonoid glycosides of great polarity from Hydrocotyle sibthorpioides Lam (HSL), the large polar flavonoid glycosides were extracted with n-BuOH, purified by DM 301 macroporous resin, Sephadex LH-20 and reversed-phase silica gel (ODS/RP-18). Combined with offline two-dimensional high-speed counter-current chromatography (HSCCC), the fraction with the target compounds was purified by HSCCC adopting a two-phase solvent system consisting of n-hexane/n-BuOH/water/glacial acetic acid (system I: 1:2:1:0.1, v/v/v/v and system II: 1:1:1:0.1, v/v/v/v). Additionally, the rotation velocity, and flow rate in conjunction with detection wavelength were adjusted to 2.0 mL/min, 900 r/min, and 254 nm respectively. The results demonstrated that four compounds were isolated from HSL, whose structures were determined as myricetin 3,3'-di-α-L-rhamnopyranoside (1), luteolin-7-O-β-D-glucuronide (2), quercetin 3,3'-di-α-L-rhamnopyranoside (3) and apigenin 7-O-β-D-glucuronide (4) operating 1H NMR and 13C NMR spectroscopy. The purity of the four compounds were above 95% by HPLC analysis, and compound 3 was isolated from the HSL for the first time. Thus, this work would provide a basis for the study of the chemical constituents of HSL.